ANALYSIS AND OPTIMIZATION OF BLOOD-TESTING PROCEDURES. Issue 3 (5th May 2017) - Bar-Lev, Shaul K.; Boxma, Onno; Perry, David; Vastazos, Lazaros P.
Abstract : This paper is devoted to the performance analysis and optimization of blood testing procedures. We present a queueing model of two queues in series, representing the two stages of a blood-testing procedure. Service (testing) in stage 1 is performed in batches, whereas it is done individually in stage 2. Since particular elements of blood can only be stored and used within a finite time window, the sojourn time of blood units in the system of two queues in series is an important performance measure, which we study in detail. We also introduce a profit objective function, taking into account blood acquisition and screening costs as well as profits for blood units, which were found uncontaminated and were tested fast enough. We optimize that profit objective function w.r.t. the batch size and the length of the time window.